AUTHORITY DISPUTE BETWEEN THE PARLIAMENT AND THE CONSTITUTIONAL COURT LAW NORMS IN FORMATION - Cahyowati, Rr; ., Kaharudin; Jayadi, Haeruman (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
The purpose of this study was to determine the dispute of authority of state institutions that occurred between the Parliament and the Constitutional Court in the establishment of the rule of law level legislation , with specific targets in the form of teaching materials produced in the course of Constitutional Law and Technical Regulations . Moreover , the conflict is to be averted in the future state institutions , especially the Parliament and the Constitutional Court in the establishment of the rule of law level legislation . The research method used is a normative legal research, with the method of statute approach and methods of conceptual approaches . Approach through legislation that researchers will conduct in-depth study f the constitusional of the 1945 Constitution and the laws regarding the authority of state institutions in the establishment of the rule of law level legislation . Through a conceptual approach , researchers will examine the concepts of thought from the experts / Constitutional Law expert associated with the authority of state institutions in the formation of legal norms equivalent legislation in Indonesia . Based on research conducted found : a. The institution has the authority to make legal norms level legislation based NRI Constitution of 1945 is the House of Representatives . This is in accordance with the provisions of Article 20 paragraph ( 1 ) NRI Constitution of 1945 which determines the " House of Representatives holds the power to make laws " . However, in terms of shaping the legislation , the House could not be alone but must involve the President . This is in accordance with the content of Article 20 paragraph ( 2 ) determine the " Every bill discussed by the House of Representatives and the President for approval together . b . Some of the solutions that can be done to resolve disputes between Parliament and the Constitutional authority in the formation of legal norms level legislation is to amend the 1945 Constitution NRI restrictions governing authority of the Court in a test of the Act . Another solution is to submit or ask the President to immediately issue a government regulation in lieu of law ( PERPU ) in order to address the legal vacuum caused by the cancellation of a norm ( section , paragraph , phrases ) law by the Court through its decision . In addition , the House of Representatives and the President as soon as possible to make changes to the law that the norm has been canceled by the Constitutional Court